The impact of antimicrobial stewardship interventions on appropriate use of surgical antimicrobial prophylaxis in low- and middle-income countries: a systematic review - Israel Abebrese Sefah; Sarentha Chetty; Peter Yamoah; Varsha Bangalee (Systematic Reviews)
Abstract Background Surgical antimicrobial prophylaxis (SAP) is an effective infection prevention strategy used to reduce postoperative surgical site infection. Inappropriate use of SAP is a concern in low-middle-income countries (LMICs) due to increased mortality risks, adverse reactions, re-admission rates and length of hospital stay. Antimicrobial Stewardship Programs (ASP) have been shown to be effective in improving the appropriate use of antibiotics including the use of SAP. The aim of this review was to evaluate the impact of ASP on the appropriate use of SAP and its implication on patient outcomes in LMICs. Method The protocol for this review was registered in PROSPERO. Studies published between 1st January 2010 and 31st December 2023 were searched electronically from Medline, Central Cochrane Library, web of science, CINAHL and APA PsychInfo databases. Studies were included if they assessed the impact of ASP interventions on SAP use in low- and middle-income countries (LMICs). Studies were evaluated using the Risk of Bias in Non-Randomized Studies–of Interventions (ROBINS-I) tool for non-randomized and before and after studies as well as the Cochrane Risk of Bias 2 (ROB 2) tool for randomized studies. Findings were summarized in tables. Results Twenty studies comprising of seventeen before-after studies, two interrupted time series, and one randomized controlled trial were included. Penicillins and cephalosporins were the most commonly used antibiotics for SAP. Most (50%) of the studies were conducted in Asia followed by Africa (45%). While 80% of the studies showed the impact of ASP on compliance to SAP guidelines, only 45% showed an impact on antibiotic utilization. Again, 50% and 60% showed an impact on reducing antibiotic costs and patient length of stay at hospitals respectively. Patient outcomes including rates of surgical site infections and mortality showed no significant change. The studies showed a high risk of bias mainly due to the choice of study designs. Conclusion ASP interventions in LMICs are effective in improving SAP guideline adherence, antibiotic utilization and their cost. Deliberate effort must be made to improve on the quality of future interventional studies in these settings to guide practice and encourage other LMICs to conduct such studies to assess the influence of different geographical contexts on SAP use.